An Empirical Study of HR Practices and Employee’s Engagement in Banking Sector - Hatem Ali, Helal Atef; Valliappan, Raju; Anees, Rao Tahir; Cavaliere, Luigi Pio Leonardo; Nordiana, Ahmad Nordin (Macrothink Institute, 2021)
Companies around the world are grappling about how to improve employee engagement in an organization. For businesses to achieve long-term sustainability and well-being, employees must be engaged. Employees accept the job that could help them go through the ladder of their needs starting from the basic needs like security up to self-enhancement, for instance, self-ego or self-worth. Social exchange theory has been selected for this study, because this theory provide knowledge and understanding which is related to the study of employee engagement. This study used quantitative approach. The samples of this research were 132 employees of private banks in Sana’a, Yemen. Data retrieval used a questionnaire and the responses are accumulated through the structured questionnaires.